If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4(1 + 6c) = 0 (1 * 0.4 + 6c * 0.4) = 0 (0.4 + 2.4c) = 0 Solving 0.4 + 2.4c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-0.4' to each side of the equation. 0.4 + -0.4 + 2.4c = 0 + -0.4 Combine like terms: 0.4 + -0.4 = 0.0 0.0 + 2.4c = 0 + -0.4 2.4c = 0 + -0.4 Combine like terms: 0 + -0.4 = -0.4 2.4c = -0.4 Divide each side by '2.4'. c = -0.1666666667 Simplifying c = -0.1666666667
| X^2-2y+x=0 | | z^6+5=8-z^6 | | 8-2x+1=9x+9 | | x+3+5=2x+4 | | 6x+3-5=40 | | 10(x+1)+8(x-1)=x-8 | | 4(2x-1)-6(3-x)=8 | | -5x+9y=-18 | | 3n^2+8=10n | | Mx+nx=x | | -2n+2n=6(1+6n)+7(1-7n) | | -5(0)+9y=-18 | | r-(-1)=9 | | 9(3n+3)=7(2n+4)+6 | | 6(x+8)-x=5x+4 | | -2(t-5)+4t=9t-6 | | 2x-9=2x-45 | | x(x+5)=(2x+10)(x-2) | | 5y-5+11x-1=9x+21 | | 15n-5=n+325 | | X^2+x=2y | | 9-(6y+2x)=8(x-y) | | 1+.80z=2+.75z | | 9*1+3=y | | 3y=32+5y | | 7w-11-4w=6 | | 12(x+8)-x=5x+4 | | M+3m+9m-4= | | 6(2n+3)=8(9n+6)+8 | | 3l+9-l-6= | | 4+.14x=5 | | 9y+3=3y+9 |